1981
DOI: 10.1093/nar/9.24.6647
|View full text |Cite
|
Sign up to set email alerts
|

The complete nucleotide sequence of the tryptophan operon of Escherichia coli

Abstract: The tryptophan (trp) operon of Escherichia coli has become the basic reference structure for studies on tryptophan metabolism. Within the past five years the application of recombinant DNA and sequencing methodologies has permitted the characterization of the structural and functional elements in this gene cluster at the molecular level. In this summary report we present the complete nucleotide sequence for the five structural genes of the trp operon of E. coli together with the internal and flanking regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(146 citation statements)
references
References 59 publications
2
144
0
Order By: Relevance
“…In general, similar codon preferences were observed among these reading frames, with some notable exceptions: for example, UUA and CUG for Leu were used most frequently in all but tdcC, where CUG was preferred; AUC for Ile was the dominant codon in tdcC; AAU was the most frequently used codon for Asn in tdcA and ORFX, whereas AAC was preferred in tdcB and tdcC; and GGU for Gly was used largely in tdcA. A comparison of average codon preference values for the five genes of the E. coli trp operon (27) with that of the three tdc reading frames and of ORFX shows some differences in the average frequency of codon usage (Table 3). A calculation of codon preference statistics, P (which is a measure of bias in codon usage), with the bacterial highly expressed codon usage data of Grantham et al (8), yielded P values of 0.870, 0.967, and 0.973 for tdcA, tdcB, and tdcC, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, similar codon preferences were observed among these reading frames, with some notable exceptions: for example, UUA and CUG for Leu were used most frequently in all but tdcC, where CUG was preferred; AUC for Ile was the dominant codon in tdcC; AAU was the most frequently used codon for Asn in tdcA and ORFX, whereas AAC was preferred in tdcB and tdcC; and GGU for Gly was used largely in tdcA. A comparison of average codon preference values for the five genes of the E. coli trp operon (27) with that of the three tdc reading frames and of ORFX shows some differences in the average frequency of codon usage (Table 3). A calculation of codon preference statistics, P (which is a measure of bias in codon usage), with the bacterial highly expressed codon usage data of Grantham et al (8), yielded P values of 0.870, 0.967, and 0.973 for tdcA, tdcB, and tdcC, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the polypeptides coded by tdcA, tdcC, and ORFX represent three new proteins in E. coli whose catalytic characteristics and metabolic roles remain to be uncovered. (10) 42 (14) 22 (2) 42 Ser UCU 23 (7) 26 (6) 29 (11) 12 (2) 15 UCC 16 (5) 35 (8) 29 (11) (27) are given.…”
Section: Methodsmentioning
confidence: 99%
“…Reaction (2) is catalyzed by the fl2 subunit and 50-fold more efficiently by the complex. This mutual activation is thought to arise from heterologous subunit-subunit interactions during assembly of the complex.…”
Section: -Phosphatementioning
confidence: 99%
“…Meanwhile the nucleotide sequences of the corresponding genes have been determined for E. roli [2], other enteric bacteria [3], and for Saccharomyces cerevisiae [4], showing that the amino acid sequences of the CI and / 3 polypeptide chains are highly conserved. Further, limited proteolysis has revealed that both the (x subunit ( M , 28727) and the p protomer (M, 42988) are composed of two autonomously folding structural domains that probably form the corresponding active sites at the interdomain interfaces [5 -91.…”
Section: -Phosphatementioning
confidence: 99%
“…The Nterminus of the R. graveo/ensAS(xl precursor was arbitrarily chosen as the first amino acid of the numbering scheme. Sources of sequences are: Arabidopsis thaliana, Niyogi and Fink (1992); Saccharomyces cerevisiae, Zalkin et al (1984), corrected as suggested by Crawford (1999) from positions 615 to 629; Salmonella typhimurium, Caliguri and Bauerle (1991); Escherichia coIL Yanofsky et aL (1981). The conserved sequence motif L(I./F)ES (131-134) is critical for allosteric inhibition by tryptophan (Matsui et al, 1987).…”
Section: Molecular Mass Of Native Asmentioning
confidence: 99%